2007
DOI: 10.1259/bjr/26692771
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of occupational radiation doses in interventional radiology

Abstract: Occupational radiation doses in interventional radiology can potentially be high. Therefore, reliable methods to assess the effective dose are needed. In the present work, the relationship between the personal dose equivalent, H(p)(10), the reading of a personal dosimeter and the effective dose of the radiologist were studied using Monte Carlo simulations. In particular, the protection provided by a lead apron was investigated. Emphasis was placed on sensitivity of the results to changes in irradiation conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…27 Smaller leaded glasses may solve the problem. A multitude of studies [28][29][30][31][32][33][34] have shown that thyroid shielding can reduce the patient dose to the radiosensitive organs outside of the primary beam without impacting on image quality. Additionally, unshielded radiation doses to the thyroid (scatter radiation) can vary depending on the scanning technique used.…”
Section: Discussionmentioning
confidence: 99%
“…27 Smaller leaded glasses may solve the problem. A multitude of studies [28][29][30][31][32][33][34] have shown that thyroid shielding can reduce the patient dose to the radiosensitive organs outside of the primary beam without impacting on image quality. Additionally, unshielded radiation doses to the thyroid (scatter radiation) can vary depending on the scanning technique used.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the effect of the energy shift of the radiation spectrum due to the apron is difficult to include. On the other hand, in analyses based on Monte Carlo methods, the assumptions and parameterization are not always explicit, and the setting of the parameters may not fully reflect the situation in radiological practice (Siiskonen et al 2007;Clerinx et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] revealed that the doses to medical staff in interventional radiology and cardiology may be of concern from a radiation hygiene point of view. Partial-body doses reported ranged from a few microsieverts up to a few millisieverts per procedure, with higher values occurring mainly for the hands.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have, however, shown that the exposure of staff and patient is not necessarily correlated [4] and that official exposure monitoring may underestimate the real effective dose [9,12,13,17] because the film badge, usually placed below the lead apron, does not account for the exposure of unshielded parts of the body, such as the hands or the thyroid. However, a general study of radiation exposure in medical personnel in interventional radiology workplaces at a larger number of facilities, taking the exposure of specific body regions into consideration, is still lacking.…”
Section: Introductionmentioning
confidence: 99%